Appropriate scale of hydropower development for Nepal : an analytic hierarchy process approach - Bhattarai, Shashi; Fujiwara, Okitsugu; Saeed, Khalid; Shrestha, Ram M.; Joint Japan World Bank Graduate Scholarship Program (JJ/WBGSP) (Bangkok : Asian Institute of Technology, 1997)
The work is a methodological framework for public involvement in the process of hydropower development. The framework evaluates the importance or preference of various stakeholders (actors) to the factors and sub-factors leading to the decision on the alternatives of hydropower development. The objective of this work is to recommend the most appropriate scale of hydropower development for Nepal which will minimize conflict and controversies. The framework is developed on Analytic Hierarchy Process (AHP), taking care of major actors, factors and sub-factors with the alternatives of range of the scale of development. Subjective value judgment is carried out from the stakeholders on structured pair-wise comparison questionnaire based on the procedure of AHP. Processing of the responses is conducted using the AHP based software called Expert Choice. The approach of public involvement and conflict management is new in the area of hydropower development management. The result of the study shows that the most appropriate scale of hydropower development in Nepal is Medium Scale. The resul.t also indicates that government and political people are the most sensitive among the seven actors considered.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Civil Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1997
Keywords: Water-power -- Nepal